2019 18th IEEE International Conference on Machine Learning and Applications (ICMLA) 2019
DOI: 10.1109/icmla.2019.00278
|View full text |Cite
|
Sign up to set email alerts
|

3D Deformable Convolutions for MRI Classification

Abstract: Deep learning convolutional neural networks have proved to be a powerful tool for MRI analysis. In current work, we explore the potential of the deformable convolution deep neural network layers for MRI data classification. We propose new 3D deformable convolutions (d-convolutions), implement them in VoxResNet architecture and apply for structural MRI data classification. We show that 3D d-convolutions outperform standard ones and are effective for unprocessed 3D MR images being robust to particular geometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One feasible approach is to capture the relationship between pixels within a reasonable area and suppress noise in the background. For this, we propose deformable convolution [35] to adaptively extract vessel features and strengthen the ability to refine thin vessels. This approach has achieved success in several tasks [36][37] [38][39], enabling receptive fields to automatically adapt to different sizes of vessels.…”
Section: ) Scale-aware Attention Modulementioning
confidence: 99%
“…One feasible approach is to capture the relationship between pixels within a reasonable area and suppress noise in the background. For this, we propose deformable convolution [35] to adaptively extract vessel features and strengthen the ability to refine thin vessels. This approach has achieved success in several tasks [36][37] [38][39], enabling receptive fields to automatically adapt to different sizes of vessels.…”
Section: ) Scale-aware Attention Modulementioning
confidence: 99%
“…For instance, the authors in [1] demonstrated that the prediction accuracy of the proposed DCN increases from 70% to 75% on the image semantic segmentation dataset (CityScapes). Significant prediction accuracy improvement is also observed in human motion recognition task [11] [12], action detection task [13] [14] and intelligent medical monitoring and treatment [15] [16].…”
Section: Introductionmentioning
confidence: 90%
“…It has long been demonstrated that deformable 3D convolution has a large spatial receptive field. [15] Therefore, it models spatio-temporal information efficiently. In our work, we use five ResD3D blocks to model group-wise features F g n , as shown in Fig.…”
Section: B Spatio-temporal Alignmentmentioning
confidence: 99%